Diagnostics of Air Purification Plasma Device by Spatially Resolved Emission Spectroscopy - Wanxia Zhao; Zeyad T. Alwahabi (Plasma, 2022)
A non-thermal plasma, air purification device (PlasmaShield®, MD250, Keswick, SA, Australia), was investigated using spatially resolved optical emission spectroscopy. The emission spectra were measured with two spatial dimensions to analyze and identify the transition lines of excited NO–γ (A2Σ–X2Π), N2 (C3Π–B3Π), and N2+ (B2Σ–X2Σ) systems. The N2 emission band at 337 and 316 nm were used to determine the spatially resolved vibrational temperature of N2 molecules, <semantics><msubsup>TvibN2</msubsup></semantics>. It was found that the average N2 vibrational temperatures in the x and y directions are almost the same. Two key operating parameters, supplied power and air flow, influence the N2 vibrational temperature. The results demonstrate that applying higher supplied power increases the vibrational temperature, while changes in air flow velocity do not affect the vibrational temperature values. The phenomenological plasma temperature (PPT) was also estimated from the N2 vibrational temperature. It was observed that PlasmaShield® generates excited N2 and NO only within a narrow region around the discharge electrode tip (with peak intensity below 100 µm from the tip). The study also shows no presence of excited OH*, O*, and other radicals.